An assessment of the effects of farmer irrigation practices on water losses and shortages: a case of Mutorahuku Irrigation Scheme - Matora, Luah (Midlands Sate University, 2015)
Farmer irrigation practices have contributed to reduction of irrigable area from 14.6ha to 9.6 ha at Mutorahuku irrigation scheme due to water loss and shortages in the scheme. A study carried out at the scheme showed that farmer irrigation practices also contribute much to water loss and shortages. Infield canal tail end losses were measured with a collecting bucket and a stop watch. Using the t test results showed that there is a significant difference between the observed and expected loss hence the scheme is losing a lot of water as tail end loss. About 7.644m³/hr of irrigation water is being lost due to farmer irrigation practices. Damaged and cracked conveyance canal losses reduced its efficiency from the expected 95% of lined canals to 65.2%. Observations and investigation through questionnaires and focused group discussion showed that farmer irrigation practices do not comply with the recommended techniques hence a lot of water loss and shortages. Only 44.6 % of the farmers at Mutorahuku irrigation scheme adopted the recommended irrigation techniques like the ¾ rule cut off time of siphons, use of one siphon /furrow, irrigation cycle, irrigation schedule and operations and maintenances of the scheme. This study showed that water loss in surface irrigation scheme is mainly attributed to farmer irrigation practices. Water being lost at canal tail ends can irrigate 1ha/hr more if the famers irrigate as recommended as evidenced by FAO that 5.4m³ / hour /hectare is required for irrigation in semi arid climate during the dry season. Recommendations of the study include irrigation water management trainings for the farmers, immediate rehabilitation of the conveyance canal to reduce water loss and monitoring of farmer irrigation practices so as comply with recommended irrigation techniques and achieve an effective water management.